Self-lubricating polyaryletherketone containing long-chain fluorine-containing end-capping agent, and preparation method and application thereof
Self-lubricating polyaryletherketone (PAG) materials using long-chain fluorinated end-capping agents and long-chain perfluoroalkyl end groups with methylene buffer structures have solved the problems of high friction coefficient and insufficient wear resistance of PAG materials, achieving low friction, high strength and thermal stability, and are suitable for aerospace, automotive manufacturing and electronic and electrical fields.
Patent Information
- Application Number
- CN202610504942.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-16
- Publication Date
- 2026-07-03
AI Technical Summary
Existing polyaryletherketone materials have a high coefficient of friction and insufficient wear resistance. Furthermore, existing modification methods result in decreased mechanical properties or high costs, making it difficult to effectively reduce the coefficient of friction and maintain material stability under oil-free lubrication conditions.
Self-lubricating polyaryletherketones are prepared by one-step polycondensation using long-chain fluorinated end-capping agents. Long-chain perfluoroalkyl end groups are introduced, and the methylene buffer structure is used to improve thermal stability. A dense fluorine atom layer is formed at high temperature to reduce the coefficient of friction and maintain mechanical properties.
A superhydrophobic surface was achieved, with the friction coefficient reduced to below 0.2 and the tensile strength maintained above 98 MPa. This solved the strength reduction problem caused by existing modification methods and demonstrated good thermal stability and economy.
Smart Images

Figure CN122325311A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of high-performance polymer materials and organic synthesis technology, and particularly relates to a self-lubricating polyarylether ketone containing a long-chain fluorinated end-capping agent, its preparation method and application. Background Technology
[0002] Polyaryletherketone (PAEK) is a class of special engineering plastics with excellent high-temperature resistance, chemical stability, mechanical properties, and electrical insulation properties, and it has wide applications in high-end fields such as aerospace, automotive manufacturing, and electronics. However, traditional PAEKs (such as PEEK) have low limiting PV values (pressure-velocity values) and high dry friction coefficients (typically between 0.3 and 0.4), making them prone to adhesive wear under oil-free lubrication or high-load conditions.
[0003] To improve the wear resistance and self-lubricating properties of polyaryletherketones (PAEs), existing technologies typically employ filler modification or chemical modification. Filler modification involves incorporating solid lubricants such as graphite, molybdenum disulfide, and polytetrafluoroethylene (PTFE) into the PAE matrix. While this method can reduce the coefficient of friction to some extent, it significantly decreases the material's mechanical properties (such as strength and toughness), and the poor compatibility between the filler and the matrix leads to agglomeration, affecting the stability of the material's properties. Chemical modification, on the other hand, improves surface properties by introducing specific functional groups into the PAE molecular chain. Introducing fluorine atoms is an effective method—fluorine atoms have extremely high electronegativity and a small atomic radius, which can reduce the intermolecular forces and surface energy of the material, thereby endowing it with excellent self-lubricating and wear-resistant properties. However, this method is costly, has low reactivity, and is difficult to polymerize.
[0004] Currently, the mainstream methods for reducing surface energy are mainly divided into physical filler modification and conventional fluorinated chemical modification. CN103242641A reduces the friction coefficient of polyaryletherketone matrix by adding solid lubricant polytetrafluoroethylene and nano-graphite flakes after polyethersulfone dispersion treatment. However, poor compatibility between filler and matrix is likely to occur, affecting the performance of composite materials and causing difficulties in processing and molding. CN120737327A discloses a method for preparing fluorinated polyaryletherketone, which uses bisphenol AF and difluoro monomer as raw materials for polymerization, effectively maintaining crystallinity and modulus, but the improvement in wear resistance is not significant.
[0005] The closest prior art to this invention is patent CN105330841A, which uses 3,4'-difluorobenzophenone for end-capping treatment. The principle is to use its 4'-position fluorine atom (highly active) to react rapidly with the polymer end to achieve end-capping, while the 3-position fluorine atom (lowly active / inert) is retained at the chain end. This method can effectively improve thermal stability. However, the above method has limitations: the fluorine atom density introduced by the monofluorine side group retained after the reaction is low, and the effect on reducing surface energy is limited.
[0006] In addition, existing modification methods have the following drawbacks:
[0007] The drawbacks of physical filling methods: Although adding solid lubricants such as PTFE can reduce the coefficient of friction, the weak bonding force between the filler and the matrix will lead to a significant decrease in the tensile strength and impact toughness of the material (usually by 30%-50%). In addition, the filler is prone to agglomeration during processing, causing surface defects in the product.
[0008] The limitations of conventional chemical modification: Existing fluorinated end-capping agents are typically simple phenols substituted with fluorine atoms or short-chain trifluoromethyl groups (such as 4-fluorophenol and 3-trifluoromethylphenol). Although these small molecules can introduce fluorine, their short fluorocarbon chains prevent them from forming a "shielding layer" similar to polytetrafluoroethylene (PTFE) on the material surface, thus limiting the improvement in hydrophobicity and lubricity. Furthermore, long-chain perfluoroalkyl iodides and other raw materials cannot directly react with the polyaryletherketone backbone. Summary of the Invention
[0009] Objectives of the Invention: The first objective of this invention is to provide a long-chain fluorinated end-capping agent; the second objective is to provide a method for preparing the long-chain fluorinated end-capping agent; the third objective is to provide a self-lubricating polyaryletherketone containing a long-chain fluorinated end-capping agent; the fourth objective is to provide a method for preparing and applying the self-lubricating polyaryletherketone containing the long-chain fluorinated end-capping agent. This invention aims to solve the problems of short fluorine chains and limited modification effects of existing end-capping agents, and to provide a novel long-chain fluorinated end-capping agent and its preparation method; furthermore, by utilizing this end-capping agent, a polyaryletherketone with a superhydrophobic surface and excellent self-lubricating properties can be prepared through one-step polycondensation.
[0010] Technical solution: The long-chain fluorinated end-capping agent of the present invention has the structure shown in general formula I as follows:
[0011]
[0012] Wherein, R is C4~C 10 Straight-chain or branched perfluoroalkyl groups.
[0013] Further, R is selected from any one of perfluoron-butyl, perfluoroisobutyl, perfluoron-pentyl, perfluoroisopentyl, perfluoron-hexyl, perfluoroisohexyl, perfluoro-2-ethylbutyl, perfluoron-heptyl, perfluoroisoheptyl, perfluoron-octyl, perfluoroisooctyl, perfluoro-2-ethylhexyl, perfluoron-nonyl, perfluoroisononyl, perfluoron-decyl, or perfluoroisodecyl.
[0014] Preferably, R is selected from perfluorobutyl (-C4F9) and perfluorohexyl (-C6F9). 13 ) or perfluorooctyl (-C8F) 17 ).
[0015] The preparation method of the long-chain fluorinated end-capping agent of the present invention includes the following steps:
[0016] (1) Dissolve aromatic ketone compounds containing hydroxyl groups in a polar solvent, and react with an organic base under the protection of an inert gas;
[0017] (2) After heating the product obtained in step (1), add a fluorinated alkyl compound dropwise to react; after treatment, a long-chain fluorinated end-capping agent is obtained.
[0018] Further, the fluorinated alkyl compound is selected from any one of perfluoroalkyl iodine, perfluoroalkyl bromide, perfluoroalkyl chloride, perfluoroalkyl sulfonyl fluoride, perfluoroalkyl sulfonate, perfluoroalkyl carboxylic acid ester, or perfluoroalkyl peroxide; the hydroxyl-containing aromatic ketone compound is selected from any one of 4-hydroxyacetophenone, 2-hydroxyacetophenone, 3-hydroxyacetophenone, 4-hydroxyacetophenone, 4-hydroxybenzophenone, 2,4-dihydroxyacetophenone, 4-hydroxy-3-methoxyacetophenone, 4-hydroxybutanone, or 4'-hydroxyacetophenone; the polar solvent is selected from any one of dimethyl sulfoxide, dimethylformamide, or dimethylacetamide; the organic base in the alkaline conditions is selected from any one of sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium methoxide, potassium ethoxide, potassium tert-butoxide, or sodium hydride.
[0019] Preferably, the fluorinated alkyl compound is a perfluoroalkyl iodine; the hydroxyl-containing aromatic ketone compound is 4-hydroxyacetophenone; the polar solvent is dimethyl sulfoxide; and the organic base is sodium methoxide.
[0020] Further, in step (1), the molar ratio of the hydroxyl-containing aromatic ketone compound to the organic base is (0.5-2):(1.5-4); the mass-volume ratio of the hydroxyl-containing aromatic ketone compound to the polar solvent is 0.12-0.15 g / mL; and the molar ratio of the fluorinated alkyl compound to the hydroxyl-containing aromatic ketone compound is (0.5-1.5):(0.5-2).
[0021] Preferably, in step (1), the molar ratio of the hydroxyl-containing aromatic ketone compound to the organic base is 1:(2-2.5); the mass-to-volume ratio of the hydroxyl-containing aromatic ketone compound to the polar solvent is 0.136 g / mL; and the molar ratio of the fluorinated alkyl compound to the hydroxyl-containing aromatic ketone compound is 1:1.
[0022] Preferably, the preparation method of the long-chain fluorinated end-capping agent of the present invention includes the following steps:
[0023] (1) Dissolve 4-hydroxyacetophenone in a polar solvent, add sodium methoxide under a protective atmosphere, and stir to activate and form sodium phenoxide and α-carbanion; the enolization and salt formation reactions are as follows:
[0024]
[0025] (2) Heat the system to 60-75℃ and slowly add perfluoroalkyl iodine dropwise; after the addition is complete, raise the temperature to 100-120℃ and keep the reaction at that temperature for 4-6 hours; the carbon-carbon coupling reaction is as follows:
[0026]
[0027] (3) After the reaction is complete, the reaction solution is poured into an acidic aqueous solution to precipitate a solid. This solid is then purified by recrystallization to obtain the target capping agent crystals. The acidification-reduction reaction is as follows:
[0028]
[0029] The self-lubricating polyaryletherketone containing a long-chain fluorinated end-capping agent of the present invention comprises a polyaryletherketone prepolymer and a long-chain fluorinated end-capping agent; wherein the molar ratio of the long-chain fluorinated end-capping agent to the polyaryletherketone prepolymer is (1-2.5):(1-2.0).
[0030] Preferably, the molar ratio of the long-chain fluorinated end-capping agent to the polyaryletherketone prepolymer is (1-2.0):1.
[0031] The preparation method of the self-lubricating polyaryletherketone of the present invention includes the following steps:
[0032] (1) Prepolymerization: Difluorinated monomers and bisphenol monomers are subjected to polycondensation reaction in the presence of alkaline salt-forming agents and aprotic polar solvents to obtain polyaryletherketone prepolymers;
[0033] (2) End capping: Add a long-chain fluorinated end capping agent to the product obtained in step (1) and react; after treatment, a self-lubricating polyarylether ketone is obtained.
[0034] Further, in step (1), the difluoro monomer is selected from any one of difluorobenzophenone and dichlorobenzophenone; the bisphenol monomer is selected from one or more of hydroquinone, 4,4'-dihydroxybiphenyl, bisphenol A, and phenolphthalein; the alkaline salt-forming agent is selected from one or more of anhydrous sodium carbonate and anhydrous potassium carbonate; and the aprotic polar solvent is selected from any one of diphenyl sulfone, sulfolane, and N-methylpyrrolidone.
[0035] Further, the molar ratio of the difluorinated monomer to the bisphenol monomer is (1-1.5):(0.5-2), the reaction temperature in step (1) is 150-320℃, and the reaction time is 2.0-4.0 hours; the reaction temperature in step (2) is 210-250℃, and the reaction time is 0.5-2 hours.
[0036] Preferably, the molar ratio of the difluorinated monomer to the bisphenol monomer is (1.01-1.05):1.
[0037] Preferably, the preparation method of the self-lubricating polyaryletherketone of the present invention includes the following steps:
[0038] (1) Prepolymerization: 4,4'-difluorobenzophenone and bisphenol monomers are subjected to a polycondensation reaction in the presence of an alkaline salt-forming agent and an aprotic polar solvent. The molar amount of 4,4'-difluorobenzophenone is controlled to be greater than that of the bisphenol monomers. The reaction is carried out to a predetermined viscosity to prepare a polyarylether ketone prepolymer with fluorine-terminated groups. The prepolymerization reaction is as follows (taking PEEK as an example):
[0039]
[0040] (2) End-capping: Add a fluorinated end-capping agent to the reaction system of step (1) and carry out the end-capping reaction under reflux conditions; after the reaction is completed, cool, crush, wash and dry the polymer melt to obtain the final product.
[0041] The general structural formula of the fluorinated end-capping agent is: Where R is C4~C 10 Straight-chain or branched perfluoroalkyl groups. The fluorine-containing end-capping reaction is as follows (taking PEEK as an example):
[0042]
[0043] When the polycondensation reaction in step 1 proceeds to the predetermined viscosity of the system, the reaction temperature is reduced to 230℃-250℃. Subsequently, the self-made fluorinated end-capping agent is added. The molar amount of the added fluorinated end-capping agent should be controlled at 1.5-2.0 times the theoretical remaining molar amount of terminal fluorine groups. A slight excess of end-capping agent can ensure that the grafting rate reaches more than 95%, and the excess end-capping agent can be removed by subsequent washing.
[0044] The present invention relates to the application of the self-lubricating polyarylether ketone containing perfluoroalkyl side chains in the preparation of wear-resistant structural parts, friction-reducing self-lubricating coatings, or polymer alloy compatibilizers.
[0045] Unlike existing technologies (such as conventional end-group blocking or low-temperature polyether modification), the core of this invention lies in the first-time proposal and design of a long-chain fluorinated ketone-phenol monomer with a "methylene buffer structure"; its unique mechanistic advantages are:
[0046] (1) Thermal stability: The synthesis temperature of polyaryletherketones is usually as high as 220℃-320℃. If the perfluorinated chain is directly linked to a strongly polar group using conventional methods, chain scission degradation is very likely to occur at high temperatures. In this invention, a methylene group (-CH2) is inserted between the aromatic carbonyl group and the perfluorinated alkyl group, which cuts off the electron-withdrawing inductive effect of the perfluorinated carbon chain, so that the end-capping agent can withstand polymerization environments above 300℃ without decomposition.
[0047] (2) Interface enrichment mechanism: During the polymer melt processing stage, the end groups with long-chain perfluoroalkyl groups, due to their extremely low surface energy, drive the spontaneous migration and enrichment of polymer chain segments to the material surface. Compared with ordinary trifluoromethyl (-CF3) end caps, the -CH2-CnF end caps introduced in this invention... 2n+1 Long-chain structures can form a dense layer of fluorine atoms (PTFE-like layer) on the surface of materials.
[0048] (3) Superhydrophobic and low friction: Experiments show that when the molar ratio of end-capping agent is less than 5%, the water contact angle can exceed 110° and the friction coefficient can be reduced to below 0.2, which solves the fatal defects of PTFE particles in physical blending, such as easy agglomeration, easy shedding, and significant reduction in mechanical strength.
[0049] (4) Excellent retention of mechanical strength: Although existing PTFE blending modification can reduce the coefficient of friction, it often leads to a 20%-30% decrease in the tensile strength of the material (as low as below 80MPa). This invention uses micro-end-capping technology to achieve surface self-lubrication without destroying the integrity and crystallization ability of the polyaryletherketone backbone. The water contact angle is increased to 105°, the coefficient of friction is reduced to 0.20, and the tensile strength is maintained above 98MPa. This effectively solves the industry problem of strength reduction caused by wear-resistant modification.
[0050] (5) Structural stability: The -C(=O)-CH2-R structure designed in this invention utilizes the methylene (-CH2-) to block the strong electron-withdrawing induction of the perfluorinated chain on the carbonyl group, preventing the chemical bond from breaking and enabling it to withstand the high temperature of 350℃ during PEEK processing.
[0051] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0052] (1) This invention proposes and designs a long-chain fluorinated end-capping agent with a "methylene buffer structure" for the first time. The end-capping agent has the properties of long fluorine chain, excellent modification effect and good thermal stability. Its preparation method is simple, the raw materials are readily available, and it has good prospects for industrial application.
[0053] (2) The self-lubricating polyaryletherketone prepared by the end-capping agent of the present invention has a superhydrophobic surface (high contact angle), excellent self-lubricating properties (low coefficient of friction) and good mechanical strength retention. The preparation process of this material is simple, the raw materials are readily available, and the cost is low, combining high performance and economy;
[0054] (3) The self-lubricating polyarylether ketone prepared by the present invention has broad application prospects in aerospace, automobile manufacturing and electronics and electrical fields. Attached Figure Description
[0055] Figure 1 The HPLC spectrum of 4-hydroxy-ω-(perfluoroalkyl)acetophenone, the long-chain fluorinated end-capping agent synthesized in Example 1, is shown below.
[0056] Figure 2 Image of the self-lubricating polyaryletherketone powder containing a long-chain fluorinated end-capping agent synthesized in Example 2;
[0057] Figure 3 The FT-IR comparison spectra of the self-lubricating polyarylether ketone (perfluorinated polyarylether ketone) synthesized in Example 2 containing a long-chain fluorinated end-capping agent and the uncapped polyarylether ketone in Comparative Example 2 are shown. Detailed Implementation
[0058] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0059] Unless otherwise specified, the experimental methods described in the embodiments are conventional methods; unless otherwise specified, the reagents and materials are commercially available.
[0060] Among them, commercially available polyaryletherketone (PEEK) is manufactured by Jiangsu Junhua, model 5600P coarse / fine powder; polytetrafluoroethylene (PTFE) powder is manufactured by Chemours Zonyl series micro powder MP1100E, with an average particle size of 4µm.
[0061] Performance testing methods and standards:
[0062] 1. Tensile strength: Tested according to ASTM D638 standard. Resin was injection molded into I-shaped specimens, the test temperature was 23℃, and the tensile rate was 50 mm / min.
[0063] 2. Friction and wear performance: Tested using a pin-disc friction and wear tester in accordance with ASTM G99 standard.
[0064] 1) Grinding pair: GCr15 bearing steel ring (hardness HRC60, surface roughness Ra0.1μm).
[0065] 2) Test conditions: dry friction environment, load 100N, speed 200rpm, test time 120 minutes.
[0066] 3) Wear rate calculation: Calculated based on wear volume loss, unit: mm 3 / Nm.
[0067] 3. Surface contact angle: Using an optical contact angle meter, add 5μL of deionized water at room temperature, let it stand for 30 seconds, and then measure the contact angle on both sides of the droplet. Take the average value of 5 points.
[0068] 4. High-Performance Liquid Chromatography (HPLC): A high-performance liquid chromatograph equipped with a C18 reversed-phase column and a UV detector was used. Gradient elution was performed using a chromatographic grade (or acetonitrile / water) system as the mobile phase. This was used to characterize the conversion rate of the synthesis reaction and the chemical purity of the final monomer product. The purity of the target monomer was calculated by comparing the retention times of the reaction substrate and the target product on the chromatographic column and using the peak area normalization method.
[0069] 5. Fourier Transform Infrared Spectroscopy (FT-IR): A Fourier Transform Infrared Spectrometer was used, and the sample was prepared using the potassium bromide (KBr) pellet method. The scanning range was 4000–400 cm⁻¹. -1 Used to characterize the characteristic functional groups in monomer molecules.
[0070] Example 1 Synthesis of long-chain fluorinated end-capping agents
[0071] In a reaction flask equipped with mechanical stirring and reflux condenser, anhydrous dimethyl sulfoxide (DMSO, 100 mL) and 4-hydroxyacetophenone (13.6 g, 0.1 mol) were added. Under nitrogen protection, sodium methoxide (11.0 g, 0.2 mol) was slowly added, and the mixture was stirred and activated at room temperature for 30 minutes. The temperature was then raised to 60 °C, and perfluorohexyl iodide (C6F) was slowly added dropwise. 13 I (44.6 g, 0.1 mol) was added, and the dropping rate was controlled to keep the system temperature below 75°C. After the addition was complete, the temperature was raised to 110°C and the reaction was carried out for 5 hours.
[0072] After the reaction was complete, the reaction solution was cooled to room temperature and slowly poured into ice water (approximately 500 mL) while continuously stirring. The solution was acidified with 5%–10% hydrochloric acid by slowly adding it dropwise through a constant-pressure dropping funnel to adjust the pH to 3–4, resulting in the precipitation of a pale yellow solid. The solid was filtered, and the filter cake was washed with an appropriate amount of ice water to obtain the crude product. The crude product was recrystallized from ethanol to obtain the white needle-like crystalline capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone (yield 72%).
[0073] See Figure 1HPLC chromatographic analysis (UV 269nm): The target product eluted after 3.7 min, with a residence time of 1 min. The chromatogram showed that the product peak area accounted for more than 98.5%, and there were no obvious residual peaks of the raw materials, proving that the monomer purity met the requirements for polymerization grade.
[0074] Example 2 Synthesis of self-lubricating polyaryletherketone containing long-chain fluorinated end-capping agent
[0075] (1) Feeding: Add hydroquinone (22.02 g, 0.2 mol), 4,4'-difluorobenzophenone (44.12 g, 0.202 mol), anhydrous potassium carbonate (29.0 g, 0.21 mol) and diphenyl sulfone (200 g) to the reactor.
[0076] (2) Polymerization reaction: After replacing the air with nitrogen, the temperature is raised to 180 °C and kept at the temperature for 1 hour to carry out salt formation and dehydration; the temperature is further raised to 310 °C and the reaction is carried out for about 2.5 hours until the viscosity of the system increases significantly, and polyaryletherketone prepolymer is obtained.
[0077] (3) End-capping reaction: Stop heating, cool down to 230 °C, and add the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone (5.54 g, about 0.012 mol, pre-dissolved in 20 mL diphenyl sulfone) prepared in Example 1; after adding the end-capping agent, set the 50 °C warm water reflux to prevent its volatilization, and keep the reaction at 230 °C for 1 hour.
[0078] (4) Post-processing: After the reaction is complete, the product obtained in step (3) is directly poured into 50°C warm water. After the product cools and precipitates, it is crushed, washed repeatedly with acetone and hot water, boiled, and finally vacuum dried to obtain a grayish-white powder. (See above) Figure 2 .
[0079] See Figure 3 Infrared spectrum displayed at 1685 cm⁻¹ -1 There is a ketone carbonyl peak at 1150-1250 cm⁻¹. -1 The presence of a strong CF stretching vibration peak at this point proves the successful introduction of a long-chain perfluoroalkyl side chain.
[0080] Test results: Tensile strength: 99 MPa; Water contact angle: 105°; Dry friction coefficient (load 100 N, speed 200 rpm): 0.20; Wear rate: 2.8 × 10⁻⁶ -6 mm³ / Nm.
[0081] Example 3
[0082] Example 3 uses the same synthesis method as Example 1, except that perfluorohexyl iodine (C6F) is used. 13I) Replace the equimolar amount of perfluorobutyl iodine (C4F9I) to prepare the capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone.
[0083] Example 4
[0084] Example 4 uses the same synthesis method as Example 2, except that the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone prepared in Example 4 is replaced with the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone prepared in Example 3.
[0085] Test results: Tensile strength: 98 MPa; Water contact angle: 102°; Dry friction coefficient: 0.23; Wear rate: 2.8 × 10⁻⁶ - 6 mm³ / Nm.
[0086] Example 5
[0087] Example 5 uses the same synthesis method as Example 2, except for the feeding steps, polymerization reaction, and end-capping reaction conditions. Specifically:
[0088] (1) Feeding: Add 4,4'-dihydroxybiphenyl (37.24g, 0.2mol), 4,4'-difluorobenzophenone (44.12g, 0.202mol), anhydrous potassium carbonate (29.0g, 0.21mol) and diphenyl sulfone (250g) to the main reactor.
[0089] (2) Polymerization reaction: After replacing the air with nitrogen, the temperature is raised to 180 °C and kept at the temperature for 1 hour to carry out salt formation and dehydration; the temperature is further raised to 320 °C and the reaction is carried out for about 3 hours until the viscosity of the system increases significantly, and polyaryletherketone prepolymer is obtained.
[0090] (3) End-capping reaction: Stop heating and cool down to 240 °C. Add the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone (5.54 g, about 0.012 mol, pre-dissolved in 20 mL diphenyl sulfone) prepared in Example 1. After adding the end-capping agent, set the temperature to 50 °C for reflux to prevent volatilization, and keep the reaction at 240 °C for 1 hour.
[0091] Test results: Tensile strength: 101 MPa; Water contact angle: 105°; Dry friction coefficient (load 100 N, speed 200 rpm): 0.20; Wear rate: 2.4 × 10⁻⁶ -6 mm³ / Nm.
[0092] Example 6
[0093] Example 6 uses the same synthesis method as Example 2, except for the feeding steps, polymerization reaction, and end-capping reaction conditions. Specifically:
[0094] (1) Feeding: Add bisphenol A (10.26g, 0.045mol), phenolphthalein (14.31g, 0.045mol), 4,4'-difluorobenzophenone (19.84g, 0.091mol), anhydrous potassium carbonate (12.7g, 0.092mol) and sulfolane (150g) to the reaction vessel;
[0095] (2) Polymerization reaction: After replacing the air with nitrogen, the temperature is raised to 160 °C and kept at the temperature for 1 hour to carry out salt formation and dehydration; the temperature is further raised to 210 °C and the reaction is carried out for about 1.5 hours until the viscosity of the system increases significantly, and polyaryletherketone prepolymer is obtained.
[0096] (3) End-capping reaction: Stop heating and cool down to 240 °C. Add the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone (5.54 g, about 0.012 mol, pre-dissolved in 20 mL diphenyl sulfone) prepared in Example 1. After adding the end-capping agent, set the temperature to 50 °C for reflux to prevent volatilization, and keep the reaction at 240 °C for 1 hour.
[0097] Test results: Tensile strength: 92 MPa; Water contact angle: 105°; Dry friction coefficient (load 100 N, speed 200 rpm): 0.22; Wear rate: 3.0 × 10⁻⁶ -6 mm³ / Nm.
[0098] Comparative Example 1
[0099] The synthesis method of Comparative Example 1 is the same as that of Example 2, except that the end-capping agent 4-hydroxy-ω-(perfluoroalkyl)acetophenone (5.54 g, about 0.012 mol, pre-dissolved in 20 mL diphenyl sulfone) is replaced with 4-fluoro-3-trifluoromethylphenol (2.16 g, about 0.012 mol, pre-dissolved in 20 mL diphenyl sulfone) in the end-capping reaction.
[0100] Test results: Tensile strength: 98 MPa; Water contact angle: 100°; Dry friction coefficient: 0.27; Wear rate: 3.5 × 10⁻⁶ - 6 mm³ / Nm.
[0101] Comparative Example 2
[0102] Comparative Example 2 is the same as Example 2, except that there is no end-capping reaction.
[0103] See Figure 3 Compared with the self-lubricating polyaryletherketone prepared in Example 2, the infrared spectrum showed that at 1685 cm⁻¹... -1 No ketone carbonyl peak was observed at 1150-1250 cm⁻¹. -1 There was no strong CF stretching vibration peak.
[0104] Test results: Tensile strength: 99 MPa; Water contact angle: 83°; Dry friction coefficient: 0.38; Wear rate: 3.7 × 10⁻⁶ -6 mm³ / Nm.
[0105] Comparative Example 3
[0106] Commercially available polyaryletherketone (PEEK, Jiangsu Junhua, model 5600P);
[0107] Test results: Tensile strength: 95 MPa; Water contact angle: 85°; Dry friction coefficient: 0.35; Wear rate: 3.5 × 10⁻⁶ -6 mm³ / Nm.
[0108] Comparative Example 4
[0109] Commercially available polyaryletherketone (PEEK, Jiangsu Junhua, model 5600P) powder and polytetrafluoroethylene (PTFE) powder (Chemistry Zonyl series micro powder MP1100E, average particle size 4um) were mixed at a mass ratio of 9:1 and blended using a twin-screw extruder.
[0110] Test results: Tensile strength: 78 MPa; Water contact angle: 105°; Dry friction coefficient: 0.18; Wear rate: 4.5 × 10⁻⁶ - 6 mm³ / Nm.
[0111] Comparative Example 5
[0112] Commercially available low-friction coefficient PEEK (Jiangsu Junhua, model 5600LF30, modified with carbon fiber, graphite and PTFE).
[0113] Test results: Tensile strength: 145 MPa; Water contact angle: 110°; Dry friction coefficient: 0.18; Wear rate: 2.5 × 10⁻⁶ - 6 mm³ / Nm.
[0114] Performance tests were conducted on Examples 2 and 4-6, and Comparative Examples 1-5, respectively. The specific test results are shown in Table 1.
[0115] Table 1 Performance test results of the examples and comparative examples
[0116]
[0117] Based on the test data in Table 1, the specific analysis results are as follows:
[0118] (1) Comparison of differences in long-chain fluorine structures
[0119] With the same main chain, the dry friction coefficient of the short chain (-CF3) end cap (Comparative Example 1) is 0.27, and the wear rate is 3.5 × 10⁻⁶. - 6 mm³ / Nm, significantly inferior to long-chain perfluoroalkyl-terminated (Example 2: 0.20, 2.8 × 10) -6 mm³ / Nm; Example 5: 0.20, 2.4×10 -6 (mm³ / Nm). This demonstrates that the long-chain perfluoroalkyl side chains introduced in this invention can spontaneously migrate and accumulate to the material surface during processing, forming a low surface energy lubricating layer, which significantly improves wear resistance and friction reduction.
[0120] (2) Comparison of chemical bonding and physical blending
[0121] While physically adding 10 wt% PTFE (Comparative Example 4) reduced the dry friction coefficient to 0.18, it increased the wear rate to 4.5 × 10⁻⁶. -6 The tensile strength dropped sharply to 78 MPa, while the tensile strength remained high at 99 MPa. Example 2, through end-group chemical bonding modification, achieved a dry friction coefficient of 0.20 and a low wear rate of 2.8 × 10⁻⁶ mm³ / Nm. -6 mm³ / Nm demonstrates that chemical bonding modification is significantly superior to physical blending in terms of balancing mechanical and tribological properties.
[0122] (3) Differences compared with commercially available PEEK and high-end modified materials
[0123] Comparison of pure PEEK and conventional products: Example 2 compared to Comparative Example 2 (self-made pure PEEK without end caps) and Comparative Example 3 (commercially available PEEK 5600P). Without the addition of any lubricating filler, the dry friction coefficient decreased from 0.35~0.38 to 0.20 (a reduction of approximately 45%), and the wear rate decreased from 3.5~3.7 to 2.8×10⁻⁶. -6 mm³ / Nm (reduced by about 20~25%), while the water contact angle increased from 83°~85° to 105°, indicating a significant improvement in surface hydrophobic lubricity.
[0124] Compared to commercially available high-end wear-resistant materials: Comparative Example 5 (commercially available low-friction PEEK5600LF30) has a lower coefficient of friction (0.18) and wear rate (2.5 × 10⁻⁶). -6 While achieving a tensile strength of up to 145 MPa (mm³ / Nm), this material requires the addition of multiple fillers such as carbon fiber / PTFE, resulting in high processing costs and complex processes. Furthermore, the high tensile strength often comes with a decrease in toughness. This invention, as a single homogeneous resin, eliminates the need for subsequent blending and granulation, exhibiting high purity and high flowability. While simplifying the processing, its tribological properties are approaching those of commercially available high-end modified materials (Example 5: wear rate 2.4 × 10⁻⁶ mm³ / Nm). -6mm³ / Nm is superior to that of Comparative Example 5), and the tensile strength is maintained in a reasonable range of 92~101 MPa, achieving an excellent balance between processing performance and service performance.
[0125] Comparison of Example 2 and Example 4: Both are long-chain fluorinated polyaryletherketones. The dry friction coefficient of Example 2 (0.20) is slightly better than that of Example 4 (0.23), while the wear rate is the same (both are 2.8 × 10⁻⁶). -6 The coefficients of friction (mm³ / Nm) are similar, with similar water contact angles and tensile strengths (105° / 99 MPa vs 102° / 98 MPa). This indicates that, under the same main chain structure, the amount of fluorine in the end-capping agent has a certain impact on the dry friction coefficient; the higher the fluorine content, the more significant the decrease in friction coefficient, but the effect on overall performance is not significant.
[0126] Comparison of Example 2 and Example 5: The dry friction coefficient of Example 5 is the same as that of Example 2 (0.20), but the wear rate is lower (2.4 × 10⁻⁶). -6 The wear rate (mm³ / Nm) was the lowest among all examples; the water contact angle was the same (105°), and the tensile strength was slightly higher (101MPa). This indicates that Example 5, with its more rigid main chain structure, can reduce the wear rate. Combined with Example 4, it can be determined that fluorine-containing end caps do not affect the material wear rate. The wear rate mainly depends on the main chain structure. Example 5 achieves optimal wear resistance while maintaining low friction.
[0127] Comparison of Example 2 and Example 6: The dry friction coefficient (0.22) and wear rate (3.0 × 10⁻⁶) of Example 6 were significantly lower. -6 The tensile strength (mm³ / Nm) was inferior to that of Example 2, while the water contact angle remained the same (105°), but the tensile strength was significantly reduced (92 MPa). This indicates that fluorinated end-capping is also suitable for the sulfolane / polyaryletherketone system, but the overall performance is worse than that of the diphenyl sulfone system, which depends on multiple factors such as the main chain structure and molecular weight distribution.
[0128] Comparison of Example 4 and Example 5: Example 5 is superior to Example 4 in terms of coefficient of friction (0.20 vs 0.23), wear rate (2.4 vs 2.8), and tensile strength (101 vs 98 MPa), with only a slightly lower water contact angle (102° vs 105°). This confirms that the formulation or process parameters of Example 5 are the preferred choice among the example groups.
[0129] Based on the above test results, the self-lubricating polyaryletherketone prepared by this invention can be directly processed by injection molding, extrusion or compression molding, and is particularly suitable for manufacturing the following wear-resistant structural parts:
[0130] (1) Oil-free bearings and bushings: used in food processing machinery or textile machinery to avoid lubricating oil contamination of products.
[0131] (2) Automotive transmission components: such as sealing rings and thrust washers in the gearbox, which use their high PV value characteristics to replace metal parts to reduce weight.
[0132] (3) Chemical pump valve assembly: Utilizing its hydrophobicity and chemical corrosion resistance, it is used to manufacture corrosion-resistant valve seats or pump body bushings.
[0133] In summary, the self-lubricating polyarylether ketone prepared by this invention has broad application prospects in aerospace, automotive manufacturing, and electronics and electrical fields.
Claims
1. A long-chain fluorinated end-capping agent, characterized in that, It has the structure shown in general formula I: Wherein, R is C4~C 10 Straight-chain or branched perfluoroalkyl groups.
2. The long-chain fluorinated end-capping agent according to claim 1, characterized in that, The R is selected from any one of perfluoron-butyl, perfluoroisobutyl, perfluoron-pentyl, perfluoroisopentyl, perfluoron-hexyl, perfluoroisohexyl, perfluoro-2-ethylbutyl, perfluoron-heptyl, perfluoroisoheptyl, perfluoron-octyl, perfluoroisooctyl, perfluoro-2-ethylhexyl, perfluoron-nonyl, perfluoroisononyl, perfluoron-decyl, or perfluoroisodecyl.
3. A method for preparing the long-chain fluorinated end-capping agent according to claim 1, characterized in that, Includes the following steps: (1) Dissolve aromatic ketone compounds containing hydroxyl groups in a polar solvent, and react with an organic base under the protection of an inert gas; (2) After heating the product obtained in step (1), add a fluorinated alkyl compound dropwise to react; after treatment, a long-chain fluorinated end-capping agent is obtained.
4. The method for preparing the long-chain fluorinated end-capping agent according to claim 3, characterized in that, The fluorinated alkyl compound is selected from any one of perfluoroalkyl iodine, perfluoroalkyl bromide, perfluoroalkyl chloride, perfluoroalkyl sulfonyl fluoride, perfluoroalkyl sulfonate, perfluoroalkyl carboxylic acid ester, or perfluoroalkyl peroxide; the hydroxyl-containing aromatic ketone compound is selected from any one of 4-hydroxyacetophenone, 2-hydroxyacetophenone, 3-hydroxyacetophenone, 4-hydroxyacetophenone, 4-hydroxybenzophenone, 2,4-dihydroxyacetophenone, 4-hydroxy-3-methoxyacetophenone, 4-hydroxybutanone, or 4'-hydroxyacetophenone; the polar solvent is selected from any one of dimethyl sulfoxide, dimethylformamide, or dimethylacetamide; the organic base is selected from any one of sodium methoxide, sodium ethoxide, sodium tert-butoxide, potassium methoxide, potassium ethoxide, potassium tert-butoxide, or sodium hydride.
5. The method for preparing the long-chain fluorinated end-capping agent according to claim 3, characterized in that, In step (1), the molar ratio of the hydroxyl-containing aromatic ketone compound to the organic base is (0.5-2):(1.5-4); the mass-volume ratio of the hydroxyl-containing aromatic ketone compound to the polar solvent is 0.12-0.15 g / mL; and the molar ratio of the fluorinated alkyl compound to the hydroxyl-containing aromatic ketone compound is (0.5-1.5):(0.5-2).
6. A self-lubricating polyarylether ketone containing the long-chain fluorinated end-capping agent of claim 1, characterized in that, It includes a polyaryletherketone prepolymer and a long-chain fluorinated end-capping agent; wherein the molar ratio of the long-chain fluorinated end-capping agent to the polyaryletherketone prepolymer is (1-2.5):(1-2.0).
7. A method for preparing the self-lubricating polyaryletherketone according to claim 6, characterized in that, Includes the following steps: (1) Prepolymerization: Difluorinated monomers and bisphenol monomers are subjected to polycondensation reaction in the presence of alkaline salt-forming agents and aprotic polar solvents to obtain polyaryletherketone prepolymers; (2) End capping: Add a long-chain fluorinated end capping agent to the product obtained in step (1) and react; after treatment, a self-lubricating polyarylether ketone is obtained.
8. The preparation method according to claim 7, characterized in that, The difluoro monomer in step (1) is selected from any one of difluorobenzophenone and dichlorobenzophenone; the bisphenol monomer is selected from one or more of hydroquinone, 4,4'-dihydroxybiphenyl, bisphenol A, and phenolphthalein; the alkaline salt-forming agent is selected from one or more of anhydrous sodium carbonate and anhydrous potassium carbonate; and the aprotic polar solvent is selected from any one of diphenyl sulfone, sulfolane, and N-methylpyrrolidone.
9. The preparation method according to claim 7, characterized in that, The molar ratio of the difluorinated monomer to the bisphenol monomer is (1-1.5):(0.5-2); the reaction temperature in step (1) is 150-320℃ and the reaction time is 2.0-4.0 hours; the reaction temperature in step (2) is 210-250℃ and the reaction time is 0.5-2 hours.
10. The application of a self-lubricating polyarylether ketone containing a perfluoroalkyl side chain as described in claim 6 in the preparation of wear-resistant structural parts, friction-reducing self-lubricating coatings, or polymer alloy compatibilizers.
Citation Information
Patent Citations
Polyaryletherketone-based abrasion-resistant composite material and preparation method thereof
CN103242641A
Industrialized synthesis method of end-capped modified polyaryletherketone resin
CN105330841A
Fluorine-containing polyaryletherketone, preparation method and application thereof, polymer membrane material and application thereof
CN120737327A